Drought stress reduces arbuscular mycorrhizal colonization of Poncirus trifoliata (L.) roots and plant growth promotion via lipid metabolism - Zhang, Wei; Yin, Xilong; Feng, Zengwei; Liu, Xiaodi; Zhu, Fengwa; Zhu, Honghui; Yao, Qing (Frontiers in Plant Science, 2024)
Drought stress poses increasingly serious threats to agricultural production in the era of global climate change. Arbuscular mycorrhizal (AM) fungi are well-recognized biostimulants promoting plant tolerance to drought stress. Lipids are indispensable for AM fungal colonization, however, the involvement of lipid metabolism in the drought tolerance conferred by AM fungi is largely unknown.In this study, we inoculated Poncirus trifoliata (L.) with Rhizophagus irregularis DAOM197198 under no drought stress, medium drought stress and severe drought stress, with non-inoculation under respective treatments as control. Results indicated that AM fungal inoculation significantly promoted the drought tolerance of P. trifoliata (L.), with the effect size decreasing along with drought severity.Moreover, the effect size was significantly related to arbuscule abundance. Fatty acid profiling showed that the arbuscule abundance was determined by the AM-specific phospholipids (PLs), whose biosynthesis and delivery were inhibited by drought stress as revealed by qRT-PCR of FatM, RAM1 and STR/STR2. More interestingly, AM fungal inoculation increased the lipid allocation to total PLs and the unsaturation rate of total neutral lipids (NLs), probably indicating the involvement of non-AM-specific lipids in the increased drought tolerance. Taken together, our results demonstrate that lipid metabolism in AM mediates the increased drought tolerance conferred by AM fungal inoculation, with AM-specific and non-AM-specific lipids functioning therein in different ways.